Non-contact ultra-widefield retinal imaging of infants with suspected abusive head trauma - Yusuf, I H (Eye (Lond), 2017)
PURPOSE: The purpose of the study was to audit the use of non-contact ultra-widefield retinal imaging in infants with suspected abusive head trauma (AHT) using the Optos P200MA Scanning Laser Ophthalmoscope. PATIENTS AND METHODS: A retrospective, observational case series. Ten eyes of five consecutive infants (aged 1–15 months) with suspected (or in 1 case, known) AHT referred for an ophthalmological opinion were included. Each infant underwent non-contact ultra-widefield retinal imaging using the Optos P200MA scanning laser ophthalmoscope. Optos fundus fluorescein angiography (FFA) was performed in one infant with oral sedation. The other four infants did not require sedation. The main outcome measure was the acquisition of a single, definitive ultra-widefield retinal image in each eye. Safety was audited by determining adverse changes in heart rate and oxygen saturations that required cessation of imaging. RESULTS: The Optos P200MA ultra-widefield scanning laser ophthalmoscope acquired good quality retinal images in all infants. Documentation of acute, widespread retinal haemorrhages contributed to a diagnosis of AHT in three infants. Chronic pre-macular haemorrhage and macular schisis were documented by FFA in a fourth infant. The absence of retinal haemorrhages was documented in a fifth infant contributing to the exclusion of a diagnosis of AHT. There were no adverse safety signals in any infant in this series. CONCLUSION: The Optos P200MA ultra-widefield scanning laser ophthalmoscope appears safe to use in infants with suspected AHT, providing high-quality retinal images in a single frame without ocular contact. Optos P200MA may be used as alternative to RetCam to document retinal haemorrhages in stable infants with suspected AHT.